2004
DOI: 10.1603/0022-2585-41.4.796
|View full text |Cite
|
Sign up to set email alerts
|

Landing Preference ofAedes albopictus(Diptera: Culicidae) on Human Skin Among ABO Blood Groups, Secretors or Nonsecretors, and ABH Antigens

Abstract: We demonstrated in this study that blood group O subjects attracted more Aedes albopictus than other blood groups (B, AB, and A) but were only significantly more attractive than blood group A subjects in 64 human landing tests. We collected saliva from the subjects and tested it for agglutination inhibition, categorized the subjects into secretors or nonsecretors, and studied mosquitoes' landing preferences for those groups. The mean relative percent landing on blood group O secretors (83.3%) was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 4 publications
1
24
0
Order By: Relevance
“…At those fine scales, DNA profiling of mosquito blood meals provides direct evidence for heterogeneous biting by the mosquitoes that transmit filarial worms, dengue virus, and malaria parasites [27][29]. Studies have shown that heterogeneous mosquito biting is associated with human body size [30], [31], defensive behavior [32], [33], pregnancy [34], [35], blood type [36], alcohol consumption [37], [38], and some volatile chemicals [39] found in breath and sweat [40][43]. Other studies have found that heterogeneity exists among households due to factors such as proximity to the aquatic habitats of immature mosquitoes [26], the type of house [44], [45], the prevailing direction of the wind [46], and other factors associated with mosquito movement patterns [46][48].…”
Section: Introductionmentioning
confidence: 99%
“…At those fine scales, DNA profiling of mosquito blood meals provides direct evidence for heterogeneous biting by the mosquitoes that transmit filarial worms, dengue virus, and malaria parasites [27][29]. Studies have shown that heterogeneous mosquito biting is associated with human body size [30], [31], defensive behavior [32], [33], pregnancy [34], [35], blood type [36], alcohol consumption [37], [38], and some volatile chemicals [39] found in breath and sweat [40][43]. Other studies have found that heterogeneity exists among households due to factors such as proximity to the aquatic habitats of immature mosquitoes [26], the type of house [44], [45], the prevailing direction of the wind [46], and other factors associated with mosquito movement patterns [46][48].…”
Section: Introductionmentioning
confidence: 99%
“…For a vector-borne disease, such as malaria, heterogeneity in the mixing rate is often a result of host-related factors, such as differential attractiveness to mosquitoes (e.g. Port et al, 1980;Shirai et al, 2004;Lindsay et al, 2000) or the use of bed nets (Lengeler et al, 2004). Heterogeneity in the mixing rate for sexually transmitted infections can be affected by including rate of sexual partner change, sexual practices (Joseph Hotz Avner Ahituv and Philipson, 1996), and access to condoms (Chimbindi et al, 2010;MacPhail et al, 2009;Bassett and Mhloyi, 1991;Pettifor et al, 2004).…”
Section: Mixing Ratementioning
confidence: 99%
“…Malaria is a well known example of a disease with heterogeneity in the mixing rate: some hosts are more attractive to mosquitoes for a variety of reasons, including body size (Port et al, 1980), blood type (Shirai et al, 2004), pregnancy (Lindsay et al, 2000;Ansell et al, 2002), and alcohol consumption (Shirai et al, 2002;Lefèvre et al, 2010), among others. An example of a directly transmitted disease with heterogeneity in the mixing rate of infected individuals is SARS.…”
Section: Mixing Ratementioning
confidence: 99%
“…Among the preference for human ABO blood groups, Anopheles gambiae has shown attraction to AB group [10] and the Ae. albopictus to O group [11]. However, the influence on blood type for mosquito fecundity has not been reported.…”
Section: Introductionmentioning
confidence: 99%